On the morphological relations of the Achilles tendon and plantar fascia via the calcaneus: a cadaveric study - A. Singh (Nature Portfolio, 2021)
Abstract Current treatments of plantar fasciitis are based on the premise that the Achilles tendon (AT) and plantar fascia (PF) are mechanically directly linked, which is an area of debate. The aim of this study was to assess the morphological relationship between the AT and PF. Nineteen cadaveric feet were x-ray imaged, serially sectioned and plastinated for digital image analyses. Measurements of the AT and PF thicknesses and cross-sectional areas (CSA) were performed at their calcaneal insertion. The fiber continuity was histologically assessed in representative subsamples. Strong correlations exist between the CSA of the AT and PF at calcaneal insertion and the CSA of PF’s insertional length (r = 0.80), and between the CSAs of AT’s and PF’s insertional lengths. Further correlations were observed between AT and PF thicknesses (r = 0.62). This close morphological relationship could, however, not be confirmed through x-ray nor complete fiber continuity in histology. This study provides evidence for a morphometric relationship between the AT and PF, which suggests the presence of a functional relationship between these two structures following the biological key idea that the structure determines the function. The observed morphological correlations substantiate the existing mechanical link between the AT and PF via the posterior calcaneus and might explain why calf stretches are a successful treatment option for plantar heel pain.